2022
DOI: 10.1021/acsami.1c23614
|View full text |Cite
|
Sign up to set email alerts
|

Plate-Like ZSM-5 Zeolites as Robust Catalysts for the Cracking of Hydrocarbons

Abstract: Zeolites with good acid site accessibility and high diffusion rates are highly desirable catalysts, especially when dealing with bulk molecules. In this work, ZSM-5 zeolites with similar Si/Al ratios but different thicknesses along the b-axis (from ∼30 nm to ∼5 μm), namely, two plate-like ZSM-5 zeolites and two reference zeolites have been prepared and the impacts of b-axis thickness on the surface properties and catalytic cracking performances are explored. Comprehensive physiochemical studies demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…It is observed that all of the samples exhibit characteristic diffraction peaks attributed to the MFI topology of the typical ZSM-5 phase. These high-intensity peaks also demonstrate that these samples are well-crystallized ZSM-5 zeolites . However, the diffraction peaks of Pt (prominent peaks should be at 2θ = 39.8, 46.2, and 67.4°) are not detected over Pt-load samples.…”
Section: Resultsmentioning
confidence: 79%
“…It is observed that all of the samples exhibit characteristic diffraction peaks attributed to the MFI topology of the typical ZSM-5 phase. These high-intensity peaks also demonstrate that these samples are well-crystallized ZSM-5 zeolites . However, the diffraction peaks of Pt (prominent peaks should be at 2θ = 39.8, 46.2, and 67.4°) are not detected over Pt-load samples.…”
Section: Resultsmentioning
confidence: 79%
“…It is generally accepted that the SiOHAl groups (corresponding to Si­(1Al,3Si)) can offer Brønsted acid sites and strong acid sites for zeolites and SiOH can offer weak acid sites. It is interesting to note that zeolites prepared with OSA show a higher content of Si­(1Al,3Si) and SiOH sites (Figure S1) compared with Blank-Z5, leading to the increase of acid amount. , According to 29 Si MAS NMR spectra, we can conclude that OSA can modulate the coordination environment of Si in zeolites and thus promote the formation of acid sites.…”
Section: Resultsmentioning
confidence: 94%
“…[15][16][17][18] H-forms of ZSM-5 (HZSM-5), as a typical MFI zeolite, is widely used in the field of petrochemical catalysis and has unique advantages in high specific surface area and adjustable acid properties. [19][20][21][22] Remarkably, the acid properties of HZSM-5, including the amount, type, strength, and distribution of acid sites, could be facilely modulated by altering the SiO 2 /Al 2 O 3 ratio (SAR). [23][24][25][26] In addition, the hydrophilicity or hydrophobicity of the surface can also be adjusted accordingly.…”
Section: Introductionmentioning
confidence: 99%